Enhancing Environmental Awareness through STEAM-Based Learning with ESD Principles in Elementary Education - Bramianto Setiawan; Awalina Barokah; Dea Nur Hafifah; Vina Iasha (International Journal of Education and Learning Studies, 2025)
This study aimed to examine the effectiveness of the STEAM approach implemented with principles of Education for Sustainable Development (ESD) in improving elementary students' environmental awareness. A quantitative method was used with a one-group pretest-posttest design. Thirty fifth-grade students participated in a four-week project-based learning program. The results showed an increase in the average environmental awareness score from 69.5 (pretest) to 83.2 (posttest), with a significance value of p = 0.000 < 0.05. Project-based learning that applied ESD principles within a STEAM approach helped students understand environmental issues concretely and encouraged pro-environmental attitudes. The study concludes that integrating ESD principles into STEAM-based learning is effective in fostering early environmental awareness. The implication is that this model can be adopted as a contextual learning strategy in primary education.